Almost Sure Exponential Stabilization of a Class of Uncertain Stochastic Systems with Markovian Switching. Issue 3 (23rd July 2014) - Zhu, F.; Han, Z.
Abstract This paper is concerned with the almost sure exponential stabilization of a class of uncertain stochastic systems with Markovian switching. A new criterion for testing the stability of such systems is established. The approach is based on stationary distribution theory. A sufficient condition is proposed for the design of robust state‐feedback controllers. An example illustrates the proposed techniques.